2017
DOI: 10.1016/j.ijrobp.2017.07.040
|View full text |Cite
|
Sign up to set email alerts
|

National Population-Based Study Comparing Treatment-Related Toxicity in Men Who Received Intensity Modulated Versus 3-Dimensional Conformal Radical Radiation Therapy for Prostate Cancer

Abstract: Prostate cancer patients who received radical radiation therapy using IMRT were less likely to experience severe GI toxicity, and they had similar GU toxicity compared with those who received 3D-CRT. These findings in an unselected "real-world" population support the use of IMRT, but further cost-effectiveness studies are urgently required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 32 publications
0
34
1
Order By: Relevance
“…More recently, a population-based study of 6933 prostate cancer patients treated with IMRT in the United Kingdom found that the incidence of gastrointestinal toxicities was low in the first nine months after radiation therapy; the highest rates were noted between nine months and approximately 2.5 years. 12 SpaceOAR use was not a consideration in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, a population-based study of 6933 prostate cancer patients treated with IMRT in the United Kingdom found that the incidence of gastrointestinal toxicities was low in the first nine months after radiation therapy; the highest rates were noted between nine months and approximately 2.5 years. 12 SpaceOAR use was not a consideration in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the multicentre study of Schmid et al found the majority of late gastrointestinal side effects (≥grade 2) occurred within 9–60 months after three‐dimensional radiotherapy (70−74 Gy) with a peak at 24 months. More recently, a population‐based study of 6933 prostate cancer patients treated with IMRT in the United Kingdom found that the incidence of gastrointestinal toxicities was low in the first nine months after radiation therapy; the highest rates were noted between nine months and approximately 2.5 years . SpaceOAR use was not a consideration in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…year. Further evaluation after a longer follow-up period is required [18]. The limited number of patients also constitutes a weakness.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding toxicity between IMRT ( n = 6933) and 3D‐CRT ( n = 16 289), Sujenthrian et al . reported the results from a national population‐based study . The use of IMRT, as opposed to 3D‐CRT, increases from 3.1% in 2001 to 64.7% in 2013.…”
Section: Clinical Results Of Imrt For Prostate Cancermentioning
confidence: 99%